Critical thinking and digital literacy: A vital relationship in the initial training of future teachers - Villa López, Roxana Marlene; Salinas Agüero, Percy Adam; Dolorier Zapata, Rosa Guillermina; Amancio Escalante, Pati Mariela (Revista de Ciencias Sociales, 2025)
Digital literacy and critical thinking are intrinsic and complementary skills. Currently, the management of digital skills is essential to access the diverse and abundant virtual information; it is a necessary input to have the cognitive support to process, interpret, and evaluate new information, which will be transformed into new knowledge. The objective of this research was to establish the correlation between digital literacy and critical thinking among students at a public university in Peru, which trains future professionals for regular basic education at the initial level. The sample consisted of 115 students from the Faculty of Early Childhood Education, who were administered two questionnaires that were validated by the statistical reliability coefficient. The results indicate a positive and significant correlation between digital literacy and critical thinking, specifically around the skills of evaluation, criticality, analysis, and synthesis of the information consumed. Based on the research conducted, it is concluded that the higher the level of digital literacy, the more complex and developed critical thinking tends to be.